Biguanides, anion receptors and sensors. Issue 72 (29th August 2017) - Pushina, Mariia; Anzenbacher, Pavel
Abstract : Biguanides are strong bases (p K a > 10), their protonated forms bind anions and may therefore act as receptors for anions. Abstract : Biguanides are strong bases (p K a > 10), their protonated forms bind anions and may therefore act as receptors for anions. We report on easy-to-make anion receptors and fluorescence-based sensors utilizing the biguanide moieties that respond to the presence of anions with a change in fluorescence. The observed changes in fluorescence are anion-specific and even though the biguanide receptors are cross-reactive, these sensors may be used to identify various anions (halides, carboxylates, phosphates). Paper-based analytical arrays were used to assess the discriminatory ability of the sensors in the qualitative and quantitative analysis of multiple anions.